Sensitive NMR approach for determining the binding mode of tightly binding ligand molecules to protein targets - Chen, Wan-Na; Nitsche, Christoph; Pilla, Kala Bharath; Graham, Bim; Huber, Thomas; Klein, Christian D.; Otting, Gottfried (Journal of the American Chemical Society, 2016)
Structure-guided drug design relies on detailed structural knowledge of protein-ligand complexes, but crystallization of cocomplexes is not always possible. Here we present a sensitive nuclear magnetic resonance (NMR) approach to determine the binding mode of tightly binding lead compounds in complex with difficult target proteins. In contrast to established NMR methods, it does not depend on rapid exchange between bound and free ligand or on stable isotope labeling, relying instead on a tert-butyl group as a chemical label. tert-Butyl groups are found in numerous protein ligands and deliver an exceptionally narrow and tall 1H NMR signal. We show that a tert-butyl group also produces outstandingly intense intra- and intermolecular NOESY cross-peaks. These enable measurements of pseudocontact shifts generated by lanthanide tags attached to the protein, which in turn allows positioning of the ligand on the protein. Once the ligand has been located, assignments of intermolecular NOEs become possible even without prior resonance assignments of protein side chains. The approach is demonstrated with the dengue virus NS2B-NS3 protease in complex with a high-affinity ligand containing a tert-butyl group.